UPAYA PENCEGAHAN PENULARAN COVID-19 DENGAN MELAKUKAN BATUK YANG BENAR DAN KEBERSIHAN CUCI TANGAN DI KOMUNITAS KELUARGA DI DESA PEKUNCEN KECAMATAN WIRADESA KABUPATEN PEKALONGAN - Ade Irma Nahdliyyah; Jihan Febrina Adella (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
COVID-19 is a disease caused by a new coronaviru strain. "CO" is taken from corona, "VI" virus, and "D" disease. Previously, the disease was called the '2019 novel coronavirus' or '2019-nCoV.' The COVID-19 virus is a new virus that is related to the same virus family as Severe Acute Respiratory Syndrome (SARS) and several types of common cold viruses. Etiology of COVID-19 severe acute respiratory syndrome coronavirus 2 (SARS-COV V-2): the 2019 coronavirus is different from SARS-CoV, but shares the same host receptor: human protective enzyme 2 (ACE2). From the observation process, the identification of physiotherapy problems in CPVID-19 by Lecturers and Students of the D-III Physiotherapy Study Program of the Faculty of Health Sciences,PekalonganUniversitywas carried out by interviewing the local community. Information obtained was in the form of problems, namely that there are still many people who do not know how to handle and prevent COVID -19. The observation process to identify physiotherapy problems in COVID-19 uses an assessment method. The purpose of this activity is to increase knowledge and understanding from the public, especially in knowing about the prevention of COVID-19 by means of good cough etiquette and how to wash hands properly for virus prevention. The solution offered by the team is to use counseling and training on how to prevent COVID-19 with good cough etiquette and proper hand washing. Five people participated in outreach and training activities. Prior to the extension and training process, the community had been given a pre-test and post-test proving that the level of public understanding had increased after being given counseling in efforts to prevent COVID-19.Keywords : Prevention of COVID-19, proper coughing and hand washing hygiene.